Matrix Metalloproteinases, Synaptic Injury, and Multiple Sclerosis - Szklarczyk, Arek; Conant, Katherine (Frontiers in Psychiatry, 2010)
Multiple sclerosis (MS) is a disease of the central nervous system in which immune mediated damage to myelin is characteristic. For an overview of this condition and its pathophysiology, please refer to one of many excellent published reviews. To follow, is a discussion focused on the possibility that synaptic injury occurs in at least a subset of patients, and that matrix metalloproteinases (MMPs) play a role in such.